Analisa Potensi Bahaya Kerja dengan Metode HIRARC pada Pekerjaan Unit FInish Mill di PT. Semen Indonesia (Persero) Tbk. Pabrik Tuban - Ilham Alamsyah, Moch; Putri F, Ardana (Universitas Bojonegoro, 2022)
The rapid advancement of technology in the industrial sector apart from having a positive impact on economic development and the prosperity of the nation also has potential hazards that can cause accidents, fires or explosions and environmental pollution. Therefore it is necessary to have efforts to prevent and control work-related accidents and diseases in companies by referring to Law Number 1 of 1970 concerning Work Safety and the regulations derived and related to this matter. This study aims to determine the application of K3 in the company and the potential for work hazards as well as to determine risk control that occurs in the Finish Mill Unit of PT. Semen Indonesia (PERSERO) Tbk. Tuban Plant based on hazard identification and hazard assessment. Data collection methods in this study are observation and reference. While the data analysis method uses the HIRARC (Hazard Identification, Risk Assessment & Risk Control) method. Based on the research results, it can be seen that in general PT. Semen Indonesia (Persero) Tbk. The East Java Tuban Factory has met statutory requirements in the scope of work safety including Personal Protective Equipment (PPE). Based on the results of the research, suggestions that can be conveyed are that it is necessary to carry out monitoring and review of the effectiveness of controls that have been implemented as a reference for continual improvement measures at certain time intervals.